Motor deficits and brain pathology in the Parkinson’s disease mouse model hA53Ttg - Breznik, Livia; Daurer, Magdalena; Rabl, Roland; Loeffler, Tina; Etxeberria-Rekalde, Estibaliz; Neddens, Joerg; Flunkert, Stefanie; Prokesch, Manuela (Frontiers in Neuroscience, 2024)
BackgroundParkinson’s disease (PD) is a debilitating neurodegenerative disorder characterized by the progressive loss of dopaminergic neurons and the accumulation of α-synuclein (α-syn) aggregates. The A53T missense point mutation occurs in autosomal dominant familial PD and has been found to promote the aggregation of α-syn. To investigate the role of the A53T mutation in PD, researchers have developed various mouse models with this mutation.ObjectiveWe therefore conducted a comprehensive characterization of the tg(THY1-SNCA*A53T)M53Sud mouse model (hA53Ttg mice) for its motor and pathological features.MethodshA53Ttg mice were tested for motor impairments in a series of motor tests at 2, 4 or 6 months of age. Human α-syn and α-syn pSer129, as well as GFAP and Iba1 signal were labeled and quantified in the cortex, hippocampus, and brainstem. Neurofilament light chain (NF-L) levels were measured in the cerebrospinal fluid (CSF) and plasma. Ex vivo analyses were performed at the age of 2, 4, 6, and 10 months.ResultsBehavioral tests revealed early muscle weakness and motor impairments that progressed with age. Immunohistochemical analyses demonstrated elevated levels of human α-syn and α-syn pSer129 in all evaluated brain regions. α-syn pSer129 labeling further revealed fiber-like structures in the cortex of older animals. Neuroinflammation was observed in an age-dependent manner. Biochemical evaluation revealed elevated NF-L levels in the plasma and CSF. Overall, our findings highlight the value of hA53Ttg mice in modeling PD-associated pathologies that closely resemble those observed in PD patients.ConclusionOur results thus suggest that hA53Ttg mice are a useful tool for studying the underlying mechanisms of PD.